MARKET ORIENTATION: IMPORTANCE, EVOLUTION, AND EMERGING APPROACHES USING SCIENTOMETRIC ANALYSIS - Gersson Torres; Sebastián Robledo; Sandra Rojas Berrío (Revista Criterio Libre, 2021)
The purpose of this review is to explore the importance, evolution, and emerging approaches to market orientation. The method had three steps: irstly, the importance of the topic was analyzed through the main scientometric metrics such as the number of publications per year; secondly, tree of science algorithm was applied to understand evolution. And thirdly, a citation analysis was performed to generate the approaches. The results show three approaches: product innovation, organization performance, and internal market orientation. This study used only one dataset to find the relevant literature; future studies could perform analysis with Scopus and Dimensions. Subsequent studies could identify different perspectives through qualitative methods with case studies to validate the findings of the present investigation.